Effect of endophytic bacterial antagonists against black rot disease of cauliflower caused by Xanthomonas campestris pv. campestris - D.K. YADAV, DINESH SINGH*, SHRI DHAR (Indian Phytopathology, 2010)
Black rot of cauliflower caused by Xanthomonas campestris pv. campestris is very destructive disease world wide and cause great losses to the crop. Antagonistic activity was tested on nutrient sucrose agar medium in vitro by using two bioagents such as Pseudomonas fluorescens strain PF – 1 and Bacillus subtilis strain BS – 7 against X. campestris pv. campestris. The bioagents were diluted 0, 10, 100 &1000 fold and X. campestris pv. campestris diluted 0, 10, 100, 1000 & 10000 fold for testing bio- efficacy. Maximum inhibition zone (2.4 cm diameter) was formed when P. fluorescens strain PF -1 containing 4.3 × 1010 cfu/ ml and X. campestris pv. campestrs diluted 10000 fold. B. subtilis formed inhibition zone 3.0 cm diameter when its population was maximum (6.4 × 1010 cfu/ ml) and X. campestris pv. campestrs diluted 10000 fold. The inhibition zone was increased with diminishing the population of X. campestris pv. campestrs by using both the antagonists. In foliar application of bioagents and antibiotics, five treatments viz., PF- 1, BS- 7, PF- 1 + BS- 7, streptomycine sulphate (Str) – 250 ppm, and control (sprayed only X. campestris pv. campestrs) were applied on 45 days old plants of cauliflower variety Pusa Snowball at three different times such as bioagent applied one week before pathogen inoculation, bioagent inoculated simultaneously before pathogen inoculation and bioagent inoculated after 3 days of pathogen inoculation. Minimum disease incidence (37.6%) and severity (1.99) found in PF- 1 + BS – 7 after 30 days of inoculation and at par to the antibiotic streptomycin sulphate 250 ppm application when it was inoculated one week before and simultaneously before pathogen inoculation. Combinationof both the bioagents may be applied for better management of black rot diseases.